Detection of radial velocity variability of HD 16673 with TIGRE. Issue 1 (27th December 2017) - Mittag, M.; Hempelmann, A.; Fuhrmeister, B.; Czesla, S.; Schmitt, J. H. M. M.
Abstract: During our TIGRE activity monitoring of late‐type stars, large radial velocity (RV) variations in the F‐type star HD 16673 were noticed. An automatic pipeline procedure using data in the wavelength range from 6000 to 7900 Å was developed and telluric lines are used as reference to determine accurate radial velocities. The RV curve demonstrates the binary nature of the HD 16673 system and allows the determination of the orbital parameters of the system. Based on the derived mass function, we obtain inclination‐dependent mass estimates for the secondary component, which orbits with a period of 37.09 days in a slightly eccentric orbit and is probably a late‐type star.